Children Victims and Witnesses of Crime - TASTANOVA, Malika Meirambekovna; KONUSSOVA, Venera Tuleutaevna; NIGMETOVA, Aizhan Sagadievna; YELEUSSIZOVA, Indira Karzhaubaevna; MUHAMEDZHANOVA, Dana Utegenovna (Journal of Advanced Research in Law and Economics, 2016)
Nowadays, the notion of the child rights is not any more distant, understandable and threatening. For decades, it was quite normal and acceptable to speak about the protection of children. That was a result of state laws, policies and attitudes, which perceived the child as a weak, immature and incapable human being on a path to adulthood. On this occasion, the child needs adult protection and guidance and society is supposed to feel and act upon solidarity, compassion and common sense. In the meantime, while all around the World adults slowly gained recognition of their human rights, children legged behind, having been left in a vast pot of ‘human beings’. In theory, men, women, children, disabled, migrant workers and others (such as elderly, indigenous, disappeared, tortured and discriminated) are all human beings and general recognition with respect for their rights should be sufficient. In practice, each of these groups felt general recognition that is not sufficient and efforts were made to distinguish specific groups and individuals as right holders. Therefore, now we can not talk only about human rights but we should also talk about the women rights, children rights, rights of disabled, etc. The difference or specificity must be identified to distinguish each group of people. Besides, the logic of human rights implies that identification of a person belonging to a specific group is necessary when there is a discrimination which leaves that person out of general application of human rights standards. So, one of the first task in this paragraph is to provide an answer to the questions: what is that specific provided to the child that makes him or her different from the rest (adults) and why special protection, as well as specific rights is required? Every year millions of children become the victims of the crimes, such as sexual and physical abuse and exploitation, trafficking, recruitment and used in armed conflicts. The CRC including its Optional Protocols States Parties have the legal obligation to take all appropriate measures to promote physical and psychological recovery and social reintegration of these children. The States Parties are encouraged to raise the standards and enable such laws and practices that would realize child rights in all situations. That in particular applies to children who are in such difficult circumstances as being victims or witnesses of violence, including crimes. Therefore, the aim of the Committee in cooperation with governmental and non-governmental actors is to encourage and support the introduction and implementation of the highest standards in this area. The Committee also committed to strive and develop its working methods, including related improvement and better targeting of its Concluding Observations, as well as to pursue even closer cooperation in this matter with other human rights treaty bodies and international, regional and national judiciary and monitoring mechanisms. Today, the issue of children victims and witnesses of crime including a crime is engaged to the agenda of the Committee, moreover it becomes more and more evident that this issue becomes important and unavoidable agenda.